Features of using low-pass filter for small signal demodulation in phase-locking motor drive - A. V. Bubnov; A. M. Daynovich (Омский научный вестник)
Phase-locking motor drive based on phase-lock principal provides high accuracy and wide shaft speed range. А low-pass filter is used for PWM-signal demodulation in phase-lock loop. This type of demodulator limits loop bandwidth and working range of motor drive. The main purpose of this article is to analyze low-pass filter influence on motor drive dynamic characteristics in low shaft speed area. The authors developed Matlab Simulink model to researcher phase-locking motor drive working in synchronous mode. As a result the dependence of angular velocity ripple versus rotational speed is obtained. The choosing condition of low-pass filter time constant is defined for different shaft speed area by using the obtained dependence. The received results can be applicable for design precision phaselock motor drive.